2003
DOI: 10.1038/oby.2003.77
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Leptin Levels and 24‐Hour Blood Pressure in Obese Women

Abstract: GUAGNANO, MARIA T., MARIA R. MANIGRASSO, ENZO BALLONE, ROSANNA DELLA VECCHIA, GRAZIANO RICCIONI, MARINA MARINOPICCOLI, MICHELE NUTINI, SERGIO SENSI, AND GIOVANNI DAVÌ. Association between serum leptin levels and 24-hour blood pressure in obese women. Obes Res. 2003; 11:549 -555. Objective: To assess the relationship between serum leptin and 24-hour blood pressure (BP) in obese women, according to body fat distribution. Research Methods and Procedures:A cross-sectional study was carried out in a population of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Indeed, after this adjustment, the associations between leptin and SV, CO and C W disappeared, but a negative association with DBP became apparent and the negative association with TPR remained. These results were confirmed by means of multiple regression analyses (Table 3 What is known about leptin and cardiovascular function (a) Leptin correlates with body fat mass and is invariably elevated in obese compared to lean subjects 6 (b) Leptin has been found to be positively associated with blood pressure in various population groups [8][9][10][11][12][13] (c) Leptin is independently associated with systolic blood pressure, pulse pressure and arterial compliance in obese hypertensive African women 21 (d) Leptin has pressor effects by: K Decreasing vascular function 14 Leptin is independently associated with intima media thickness of the common carotid artery 15 and decreased arterial distensibility, decreasing arterial compliance 14 This is possible since leptin receptors are situated on the endothelium 35 and vascular smooth muscle cells 36 K Increasing renal sympathetic activity:…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Indeed, after this adjustment, the associations between leptin and SV, CO and C W disappeared, but a negative association with DBP became apparent and the negative association with TPR remained. These results were confirmed by means of multiple regression analyses (Table 3 What is known about leptin and cardiovascular function (a) Leptin correlates with body fat mass and is invariably elevated in obese compared to lean subjects 6 (b) Leptin has been found to be positively associated with blood pressure in various population groups [8][9][10][11][12][13] (c) Leptin is independently associated with systolic blood pressure, pulse pressure and arterial compliance in obese hypertensive African women 21 (d) Leptin has pressor effects by: K Decreasing vascular function 14 Leptin is independently associated with intima media thickness of the common carotid artery 15 and decreased arterial distensibility, decreasing arterial compliance 14 This is possible since leptin receptors are situated on the endothelium 35 and vascular smooth muscle cells 36 K Increasing renal sympathetic activity:…”
Section: Discussionmentioning
confidence: 77%
“…5 Since the adipocyte derived hormone, leptin, is invariably elevated in the obese, 6 studies have suggested the involvement of leptin in obesityrelated hypertension. 7 Rightly so, leptin has pressor actions and has been associated with blood pressure [8][9][10][11][12][13] as well as decreased vascular function, 14,15 lowering C W and increasing TPR. Furthermore, leptin also activates the sympathetic nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a strong relationship between leptin concentration and BMI (a surrogate for overall adiposity). [10][11][12][13][14][15][16][17][18] Moreover, the genetic studies revealed that the strong correlation between these two variables is a result of shared genetic sources (eg Kaprio et al…”
Section: Introductionmentioning
confidence: 99%
“…Leptin levels have been reported to be higher in patients with hypertension compared to normotensive controls 11,43 and have been positively associated with blood pressure in various nonAfrican population groups. [10][11][12][13][14][15]43 El-Gharbawy et al 8 failed to obtain a direct positive association between leptin and blood pressure in obese hypertensive African-American women with leptin levels that were significantly higher in relation to a obese normotensive African-American female group. Since leptin is independently associated with intima-media thickness, 17 decreased arterial distensibility 16 (decreasing arterial compliance) and blood pressure [10][11][12][13][14][15]43 in non-African population groups, the findings by El-Gharbawy et al 8 seems surprising since the group under study was hyperleptinaemic and hypertensive.…”
Section: Discussionmentioning
confidence: 99%
“…8 Evidence suggests that elevated leptin levels may play an important role in the pathogenesis of obesity-related hypertension 9 and accordingly has been associated with increased blood pressure. [10][11][12][13][14][15] The mechanisms associating leptin with blood pressure in obesityrelated hypertension are multiple. One mechanism has been the involvement of leptin in decreasing vascular function.…”
Section: Introductionmentioning
confidence: 99%